Sustainable and Quality Tourism Training for the Local Community of Braga Tourism Village - Baswarani, Delfta Tunjung; Desmantyo, Pandu Sapto; Bahri, Khoirun Nisa; Wibawa, Rizka Nala (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
The readiness and participation of the community in balancing their area to become a destination with quality tourism is needed. Therefore, community empowerment is needed, which aims to harmonize the existing strategic plan for the community living in Braga Tourism Village, which requires readiness and participation in its development because the community lives around an area with historical and cultural tourism potential, which of course needs to be preserved and utilized by applicable laws. The community needs to identify the potential and implement suitable programs based on the concept and applicable laws. With this provision, it was hoped that community-based tourism eﬀorts would support the existence of areas with potential cultural and historical attractions and promote quality tourism. This community service program aims to provide material on the concept of quality tourism and sustainable tourism. This program aimed to maximize the potential of the cultural history tourist attraction of Braga Tourism Village, which then targets the community to understand and apply the material that has been given in the training. The activity method is in the form of exposure to quality and sustainable tourism material to maximize existing potential. This program was divided into three parts: planning and preparation, implementation, monitoring, and evaluation. This training program was well executed because the community had better post-test score results compared to the pretest. However, they still need to learn more about the positive impact of tourism on the environment and its application in the community, especially businesses that support tourism.